Primary systemic therapy in resectable pancreatic ductal adenocarcinoma using mFOLFIRINOX: A pilot study. Issue 3 (16th October 2017) - de W. Marsh, Robert; Talamonti, Mark S.; Baker, Marshall S.; Posner, Mitchell; Roggin, Kevin; Matthews, Jeffrey; Catenacci, Daniel; Kozloff, Mark; Polite, Blase; Britto, Michele; Wang, Chi; Kindler, Hedy
Abstract : Background and Objectives: Surgery followed by gemcitabine and/or a fluoropyrimidine is standard therapy for resectable PDAC. mFOLFIRINOX (oxaliplatin 85 mg/m 2, irinotecan 180 mg/m 2, leucovorin 400 mg/m 2 Day 1, 5‐FU 2400 mg/m 2  × 48 h IV, peg‐filgrastim 6 mg SQ day 3, every 14 days) has substantial activity in metastatic PDAC. We wished to determine the tolerability/efficacy of peri‐operative mFOLFIRINOX in resectable PDAC. Methods: Patients with resectable PDAC (ECOG PS 0/1) received four cycles of mFOLFIRINOX pre‐ and post‐surgery. The primary endpoint was completion of preoperative chemotherapy plus resection. Secondary endpoints included completion of all therapy, R0 resection, treatment related toxicity, PFS, and OS. Results: Twenty‐one patients enrolled: median age 62 (47‐78); 20/21 (95%) completed four cycles of preoperative mFOLFIRINOX; response by RECIST was 1 CR, 3 PR, 16 SD; 17/21 (81%) completed resection, 16/21 (76%) R0; 14/21 (66%) completed four cycles of postoperative mFOLFIRINOX. Grade 3 and 4 toxicity occurred in 23% and 14% patients pre‐operatively, 26% and 6.0% post‐operatively. Nine patients are alive with median follow‐up of 27.7 (3.1‐47.1) months. Conclusions: PST using mFOLFIRINOX in resectable PDAC is feasible and tolerable. R0 resection rate is high and survival promising, requiring longer follow‐up and larger studies for definitive assessment.